Non-western scholars, bourgeois virtues, and the international scientific community in the age of empire, 1870-1920 - Gänger, Stefanie (The historical journal, 2024)
Historians have long argued that science was fashioned as a bourgeois, Western cultural practice by the late nineteenth century, in ways that allowed its practitioners to exclude or distance themselves - through a rhetoric of endeavour, utilitarianism, and progress - from the more useless, ‘frivolous’ learning of aristocrats, women, or, indeed, native ‘informants’ in the colonies. This article examines the case of scholars from outside northern Europe and North America - Japanese literati, creole intellectuals, and Lebanese scholars - who managed to participate in the period’s Western scientific networks as peers. It holds that these men were able to establish epistemic credibility not because their lower rung in a political and racial hierarchy was ever irrelevant, but because their status as upper-middle-class professionals and their bourgeois habitus - their ‘civility’, and ‘manners’ - in some measure made up for it. The article reveals, rather than forthright ‘exclusion’ and ‘silencing’ of non-Europeans, complex epistemic hierarchies and geographies of knowledge. It exposes the mechanisms of epistemic inclusion and its limits in the period: the functioning of an academic community that was - in many, rather significant ways - also a social world.